Causal Model of Learning Supervision on Teacher Performance: Madrasah Head, Organizational Culture, and Self-Discipline - Muhammad Yusuf; Candra Wijaya; Abdurrahman Abdurrahman (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study analyzes the direct and indirect effects of instructional supervision by the head of madrasah, organizational culture, and self-discipline on the performance of Madrasah Aliyah teachers in Gayo Lues Regency. Methodology: Using a quantitative approach with a causal model and involving 84 teachers selected through the Krejcie–Morgan sampling technique, this research employs path analysis to examine the structural relationships among the variables. Main Findings: The findings indicate that organizational culture has the strongest influence on teachers’ self-discipline (ρ = 0.436), while instructional supervision exerts a smaller but positive effect (ρ = 0.132). Teacher performance is significantly affected by instructional supervision (ρ = 0.597), organizational culture (ρ = 0.408), and self-discipline (ρ = 0.324). Although instructional supervision and organizational culture also influence teacher performance indirectly through self-discipline, these mediating effects are relatively small—0.044 and 0.132 respectively. The model fit analysis confirms that the proposed causal structure aligns well with the empirical data. This study contributes to educational management literature by offering a comprehensive model integrating supervision, culture, and self-discipline, and by establishing self-discipline as a partial mediator between organizational culture and teacher performance. Novelty/Originality of this study: The findings highlight the importance of strengthening supervisory practices, cultivating a positive organizational culture, and enhancing teacher discipline to improve professional performance in madrasahs. Overall, the study provides empirical evidence that can support the development of strategic policies to enhance teacher quality and accountability in Islamic educational institutions.